2002
DOI: 10.1037/0894-4105.16.3.322
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of Arabic orthography slow its processing.

Abstract: The present study was designed to evaluate whether the complexity of Arabic orthography increases its perceptual load, thus slowing word identification. Adolescent Arabic speakers who mastered Hebrew as a second language completed oral and visual versions of the Trail Making Test (TMT; J. E. Parington & R. G. Lieter, 1949) in both languages. Oral TMT required declaiming consecutive numbers or alternation between numbers and letters. Visual TMT required connecting Arabic or Indian numbers and alternation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 10 publications
4
93
0
Order By: Relevance
“…This pattern is attributable to the greater graphemic complexity of Urdu orthography, and is reminiscent of a similar finding reported for Arabic Ibrahim et al, 2002), whose orthography forms the basis for Urdu script.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This pattern is attributable to the greater graphemic complexity of Urdu orthography, and is reminiscent of a similar finding reported for Arabic Ibrahim et al, 2002), whose orthography forms the basis for Urdu script.…”
Section: Discussionmentioning
confidence: 55%
“…For example, the graphemes ( all represent the Arabic letter ain (IPA symbol /ʕ/). In a striking set of studies, Eviatar and colleagues found that native Arabic readers were slower to respond to CVC strings in Arabic as compared to Hebrew and English, their second and third languages respectively Eviatar, Ibrahim, & Ganayim 2004;Ibrahim, Eviatar, & Aharon-Peretz 2002). Indeed, the Arabic readers tested by Eviatar et al exhibited greater accuracy in identifying Hebrew compared to Arabic letters.…”
Section: Testing the Odh Using Hindi And Urdumentioning
confidence: 99%
“…Indeed, a number of studies have investigated the graphic characters of the Arabic script and concluded that they constitute a specific challenge to Arabic readers, particularly in terms of the ability of the reader to distinguish individual letters. For example, work by Ibrahim, Eviatar and Aharon-Peretz (2002) found that Arabic-Israeli participants were slower in processing Arabic letters than Hebrew letters, despite the fact that Arabic was the first language of the individuals tested. These researchers have concluded that such effects are due to the complexity of Arabic script compared to the Hebrew script.…”
Section: Orthographic Influencesmentioning
confidence: 99%
“…It was suggested that the complexity of Arabic orthography imposes a linguistic burden that is created by additional orthographic information in Arabic, as compared with other orthographies, such as the Hebrew orthography (Azzam, 1993;Eviatar, Ibrahim, & Ganayim, 2004;Ibrahim, Eviatar & Aharon-Perez 2002), and English orthography (Eviatar & Ibrahim, 2004). According to these studies, this linguistic burden of the Arabic orthography plays a significant role in the acquisition of the written form of Arabic, compared with other languages, and may cause a delay in the literary development and in the ability to achieve automatic reading (Ibrahim et al, 2002;Eviatar, Ibrahim, & Ganayim, 2004;Ibrahim and Aharon-Peretz, 2005). Trying to better understand the linguistic features that affect the reading process in the written form of Arabic, a recent study by Taha, Ibrahim, and Khateb (2013) among adult native Arabic skilled readers found that reaction times variance was higher and accuracy was lower in non-connected words compared with connected words.…”
Section: Phonetic and Phonological Characteristics Of Arabicmentioning
confidence: 99%
“…Several studies in the past few years have pointed out difficulties with the acquisition of the written form of Arabic among native Arabic speakers (Abu Rabia, 2001, 2002Abu Rabia & Siegel, 1995;Abu Rabia & Taha, 2004Azzam, 1984Azzam, , 1993Bentin & Ibrahim, 1996;Eviatar, Ibrahim & Ganayim, 2004;Ibrahim, Eviatar & Aharon-Perez, 2002;Saiegh-Haddad, 2003, 2004Saiegh-Haddad, Levin, Hende, and Ziv, 2011). For example, it was found that reaction times for visual recognition of Arabic words by senior high school native Arabic skilled readers were longer than reaction times for Hebrew words by native Hebrew high school seniors (Bentin & Ibrahim, 1996), English words by native English undergraduates, and Serbo-Croatian words by native Serbo-Croatians undergraduates (Frost, Katz, & Bentin, 1987).…”
Section: Phonetic and Phonological Characteristics Of Arabicmentioning
confidence: 99%